RESPONSE TO DIFFERENT CONVENTIONAL INTERFERONS IN TREATMENT OF CHRONIC HEPATITIS C - Ahmed, Waquaruddin; Arif, Ambreen; Alam, Ejaz; Qureshi, Huma (Journal of Ayub Medical College Abbottabad, 2012)
Background: Sustained virological response to interferon therapy is a great challenge for patients of chronic Hepatitis C. Over 20 brands of interferons are available in the local market with each claiming over 80% response and a wide variation in the cost thus creating confusion for treating physicians as to which drug should be selected. Methods: Chronic Hepatitis C patients attending outpatients department of Pakistan Medical Research Centre JPMC from January 1998-December 2010 were evaluated. Complete blood count, liver function tests, serum proteins, HCV-RNA were done in all cases before starting therapy. Side effects were also noted. Results: Total of 851 cases received interferon 3 MIU three times a week for 6 months. There were 638 (75%) males and 213 (25%) females, mean age was 36.1±10.4 years. All were HCV-RNA positive prior to treatment, at the end of 6 months 666 (78.3%) became negative while 185 (21.7%) were non-responders with positive HCV RNA. End of treatment response (ETR) showed 84.7% with Bioferon (Argentina), 83.8% Hebron (Cuba), 82.2% INF (Argentina), 82.1% Ceron (China), 81% Viteron (Korea), 80.7% Leveron (Argentina), 81.5% Hepaferon, 79.1% Anferon (China), 77.4% Intron (Belgium), 75% Green alpha (Korea), 74% Roferon (Switzerland), 67.3% Uniferon (Lithuania), and 68.4% with others. Post-treatment 211 cases were lost to follow-up. In remaining 358/640 (55.9%) negative for HCV-RNA, at six months follow up, whereas 98 (15.3%) relapsed. Sustained virological response (SVR) Ceron 68.2%, Hebron 66.3%, Bioferon 65.2%, Leveron 60.5%, Intron 60.3%, Viteron 57%, Anferon 53.3%, Green alpha, Roferon, Hepaferon, and others 50%, INF 48.5% and Uniferon 41.9%. Average cost of these interferons was Rs. 6,000/month, except Hepaferon 5,000/month, Roferon 10,600/month. Conclusions: ETR ranged from 74-84.7% and SVR 41.9% to 68.2% and >60% SVR was observed with Ceron, Hebron, Bioferon, Leveron, Intron and were cost effective. Keywords: Conventional interferon, response, chronic Hepatitis C.